INFLUENCES OF TIME AND RATIO OF Si/Al ON FORMATION ZEOLITE A FROM BOTTOM ASH CARBON FREE PLTU PT. IPMOMI WITH HYDROTHERMAL METHODS - R. A. Syukuri Nikmah; Nurul Widiastuti; Hamzah Fansuri (Jurnal Zeolit Indonesia, 2008)
This study aimed to utilize bottom-ash PLTU PT. IPMOMI, Probolinggo. Synthesis zeolite A conducted with directly method of hydrothermal. Initially, bottom-ash calcined at temperature of 800oC during 4 hours for eliminating residu of carbon from baking of coal, then it was dissolved with alkali NaOH, NaAlO2 and water deionization with comparison molar of 3.165 Na2O: Al2O3: 1.926 SiO2: 128 H2O. Crystallization of hydrothermal conducted by variation time (12-144 hours) and ratio molar of Si/Al (1; 1.2 and 1.4). The result XRD analysis showed that kinds form of zeolite is mixture of zeolite A, X, P and sodalite. The most form dominant of Zeolite with various variations condition hydrothermal is zeolite A with orthorombik structure which was formed at hydrothermal temperature of 160°C during 24 hours.